Results of the attitude reconstruction for the UniSat-6 microsatellite using in-orbit data. (October 2016) - Battistini, Simone; Cappelletti, Chantal; Graziani, Filippo
Abstract: UniSat-6 is a civilian microsatellite that was launched in orbit on the 19th of June, 2014. Its main mission consisted in the in-orbit release of a number of on-board carried Cubesats and in the transmission to the UniSat-6 ground station of telemetry data and images from an on-board mounted camera. The spacecraft is equipped with a passive magnetic attitude control system. Gyros and magnetometers provide the information about the attitude of the spacecraft. The importance of reconstructing the attitude motion of UniSat-6 lies in the dual possibility, for future missions, of: controlling the direction of ejection of the on-board carried satellites having an accurate pointing for remote sensing operation. The reconstruction of the attitude motion of UniSat-6 is based on the data of the on-board Commercial Off The Shelf (COTS) gyros and magnetometers, downloaded at the passages over the ground station in Roma, Italy. At ground, these data have been processed with the UnScented QUaternion Estimator (USQUE) algorithm. This estimator is an adaptation of the Unscented Filter to the problem of spacecraft attitude estimation. The USQUE is based on a dual attitude representation, which involves both quaternions and Generalized Rodrigues Parameters. In this work, the propagation phase of the algorithm contains only a kinematic model of the motion of the spacecraft. This paper presents the results of the reconstruction of the UniSat-6 attitude using on-board measurements. The results show that the spacecraft effectively stabilized its attitude motion thanks to the on-board magnetic devices. Abstract : Highlights: The attitude reconstruction for the UniSat6 satellite is proposed. Attitude reconstruction is based on the data of the on-board gyros and magnetometers. The data have been processed on ground with the USQUE algorithm. UniSat6 has stabilized thanks to the passive magnetic control devices.